2007
DOI: 10.1176/appi.ajp.2007.06101645
|View full text |Cite
|
Sign up to set email alerts
|

Differences in PTSD Prevalence and Associated Risk Factors Among World Trade Center Disaster Rescue and Recovery Workers

Abstract: Workers and volunteers in occupations least likely to have had prior disaster training or experience were at greatest risk of PTSD. Disaster preparedness training and shift rotations to enable shorter duration of service at the site may reduce PTSD among workers and volunteers in future disasters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
351
4
11

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 395 publications
(393 citation statements)
references
References 32 publications
27
351
4
11
Order By: Relevance
“…From the perspective of social ethics, we need to raise awareness of occupational protection of sanitation workers and strengthen research on this vulnerable group in developing countries. There have been hardly any studies on sanitation workers in the past 30 years in developed countries, where sanitation work is mechanized [23]. From the perspective of macropolicy, China already has an excellent legal system and the central government has worked actively in the field of occupational safety and health protection.…”
Section: Comparison With Previous Studiesmentioning
confidence: 99%
“…From the perspective of social ethics, we need to raise awareness of occupational protection of sanitation workers and strengthen research on this vulnerable group in developing countries. There have been hardly any studies on sanitation workers in the past 30 years in developed countries, where sanitation work is mechanized [23]. From the perspective of macropolicy, China already has an excellent legal system and the central government has worked actively in the field of occupational safety and health protection.…”
Section: Comparison With Previous Studiesmentioning
confidence: 99%
“…that the detection rate decreases in organizations that have established hierarchies such as in fire-fighting, police, or military [6][7][8]. Some causes of undervaluation in self-administered screenings are prejudice, discrimination, resistance to mental health disorder, or anxiety on career disadvantage in the job [6].…”
Section: Special Issue On Recent Advances In Engineering Systemsmentioning
confidence: 99%
“…Besides these tests, there are proposals to use biomarkers such as saliva [7] and blood [8] as a method of evaluating mental health conditions. However, although selfreport psychometric tests are effective in determining those conditions at their early stages and in complementing diagnoses, there are issues of reporting biases.…”
Section: Introductionmentioning
confidence: 99%
“…Perrin et al (2007) found that the overall prevalence of PTSD among rescue/recovery workers was 12.4%, ranging from 6.2% for trained police to 21.2% for untrained and unaffiliated volunteers 17) . Debchoudhury et al (2011) confirmed these findings and found that unaffiliated volunteers had greater risk of early mental health diagnosis, chronic PTSD, and lateonset PTSD 18) .…”
Section: The Importance Of Worker Training In Preventing Ptsdmentioning
confidence: 99%